Alternative Splicing of MXD3 and Its Regulation of MXD3 Levels in Glioblastoma - Ngo, Tin; Corrales, Abraham; Bourne, Traci; Elmojahid, Samir; Lam, Kit S.; Díaz, Elva (Frontiers in Molecular Biosciences, 2019)
The transcription factor MXD3 is an atypical member of the MYC/MAX/MXD transcriptional network and has been previously shown to be an important regulator of cell proliferation. MXD3 has been shown to be overexpressed and to be required for medulloblastoma and acute lymphoblastic leukemia cell proliferation. In this study we leveraged datasets from The Cancer Genome Atlas to examine MXD3 across several cancers. We find that MXD3 transcripts are significantly overexpressed in ~72% of the available datasets. The gene itself is not frequently altered, while the promoter appears to be hypomethylated. We examine the possibility that aberrant regulation of the MXD3 message is the cause of abnormal MXD3 expression across cancers. Specifically, we looked at MXD3 alternative splicing in glioblastoma multiforme (GBM) and find notable functional differences between the splice variants. The 3’UTR confers differential message stability. Furthermore, the different coding sequences lead to different protein stabilities and localizations. Altogether, these data extend our knowledge of MXD3 in the context of human cancers while characterizing a previously unstudied splice variant of MXD3.